Theoretical and experimental aspects of laser cutting using direct diode laser source based on multi-wavelength multiplexing. (June 2019) - Lin, Xingchen; Wang, Pengfei; Zhang, Yawei; Ning, Yongqiang; Zhu, Hongbo
Highlights: A diode laser with an output power of 2 kW based on the multi-wavelength multiplexing is introduced. A theoretical laser cutting model is built to predict the cutting performance of a direct diode laser source. The cutting result of the diode laser is better than that of the fiber laser when the thickness of sheet is more than 3 mm. Abstract: In this paper, a theoretical laser cutting model based on absorption calculations and the characteristics of multi-wavelength laser beam is introduced to predict the cutting performance of a direct diode laser source (2 kW output power from an optical fiber with a 105 μm core diameter and a numerical aperture of 0.2). Cutting experiments are performed on stainless steel sheets (304) with thicknesses ranging from 1 mm to 10 mm. When comparing with the relevant industrial cutting results using fiber lasers, this diode laser source can obtain a greater speed at the thickness of samples above 3 mm. The experimental results have a good agreement with the theoretically predicted results and demonstrate the cutting ability of the diode laser source of such power class and brightness class for use in industrial laser cutting applications.